Agro-ecological monitoring of the territory of the Chelyabinsk agriculture research institute - Ottinger D.M.; Gusev A.S.; Inysheva V.A.; Lopukhov P.M.; Anisimov Yu.B. (BIO Web of Conferences)
Agroecological monitoring of lands is an important tool in regulating the development of unfavorable processes of lands suitable for agricultural use. It is a component of land use forecasting. The article is devoted to the organization of agroecological monitoring on the territory of the Chelyabinsk Agriculture Research Institute enterprise using methods of Earth remote sensing. This article analyzes the current state of agricultural lands of the Chelyabinsk Agriculture Research Institute with territory classification. The main focus is on monitoring the condition of crops for the growing season of 2023. The analysis of data in GIS systems allows to predict risks and take measures to increase crop yields and resistance to climate change. This direction has its relevance today. Monitoring is one of the tools for forecasting and rational land use.